2014
DOI: 10.1371/journal.pone.0098017
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Nardilysin Prevents the Development of Steatohepatitis and Liver Fibrotic Changes

Abstract: Nonalcoholic steatohepatitis (NASH) is an inflammatory form of nonalcoholic fatty liver disease that progresses to liver cirrhosis. It is still unknown how only limited patients with fatty liver develop NASH. Tumor necrosis factor (TNF)-α is one of the key molecules in initiating the vicious circle of inflammations. Nardilysin (N-arginine dibasic convertase; Nrd1), a zinc metalloendopeptidase of the M16 family, enhances ectodomain shedding of TNF-α, resulting in the activation of inflammatory responses. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…The elevated serum sVTCN1 levels (8) combined with an increased PBMCs' NRD1 expression in RA patients (52), provide an initial insight into this quest, and hint that NRD1-dependent impairment of VTCN1-mediated negative co-stimulation is a general autoimmunity-associated pathway. In agreement, systemic NRD1 deficiency was recently reported to significantly reduce liver inflammation and protect mice from diet-induced nonalcoholic steatohepatitis (53). Our results imply a possibility that stabilization of VTCN1 in liver cells of these mice is a conceivable explanation for such a phenotype.…”
Section: Discussionsupporting
confidence: 62%
“…The elevated serum sVTCN1 levels (8) combined with an increased PBMCs' NRD1 expression in RA patients (52), provide an initial insight into this quest, and hint that NRD1-dependent impairment of VTCN1-mediated negative co-stimulation is a general autoimmunity-associated pathway. In agreement, systemic NRD1 deficiency was recently reported to significantly reduce liver inflammation and protect mice from diet-induced nonalcoholic steatohepatitis (53). Our results imply a possibility that stabilization of VTCN1 in liver cells of these mice is a conceivable explanation for such a phenotype.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, we demonstrated that the production of inflammatory cytokines and the recruitment of inflammatory cells are significantly suppressed concomitant with the suppression of TNFα release on Nrdc deletion in a mouse steatohepatitis model 46. In contrast, in the present study, we showed that Nrdc is expressed in the nucleus of pancreatic acinar cells and that pancreatic Nrdc acts as a tumour suppressor for Kras G12D -driven PanIN and PDA formation most likely through blocking pancreatitis in mice.…”
Section: Discussioncontrasting
confidence: 70%
“…When choline-deficient L-amino-acid-defined or high-fat diets are administered, Nrdc -/-mice, unlike the Nrdc +/+ strain, do not develop steatohepatitis (17). NRDC has recently been identified as a dimethyl-H3K4 binding protein (18).…”
Section: Introductionmentioning
confidence: 99%